Immunological Techniques to Identify Azospirillum Associated with Wetland Rice - Ladha, J.K.; Barraquio, W.L.; Watanabe, I. (Canadian Science Publishing, 1982)
Azospirilla associated with wetland rice were isolated and characterized by employing immunodiffusion and immunofluorescence techniques. Antisera against two strains belonging to Azospirillum lipoferum produced at least one heat-labile precipitation band with most isolates of A. lipoferum and A. brasilense. Antisera against two strains belonging to A. lipoferum and one strain belonging to A. brasilense produced one band only with strains of their respective species. Fluorescent antibody reactions with Azospirillum were species specific. Specificity of these antisera and fluorescent antibodies was further demonstrated with bacteria other than Azospirillum.